Reverse End-to-Side Anterior Interosseous Nerve–to–Ulnar Motor Transfer for Severe Ulnar Neuropathy. Issue 3 (September 2020) - Doherty, Christopher D.; Miller, Thomas A.; Larocerie-Salgado, Juliana; Byers, Brett A.; Ross, Douglas C.
Abstract : Background: Reverse end-to-side anterior interosseous nerve transfer has been reported to enhance treatment of severe, proximal ulnar neuropathy. The authors report on patients with severe neuropathy treated with ulnar nerve transposition and distal reverse end-to-side anterior interosseous nerve transfer. Methods: Thirty patients with severe ulnar neuropathy at the elbow were reviewed. Clinical parameters included preoperative and postoperative Medical Research Council muscle strength, clawing, and degree of wasting. Electrodiagnostic data included compound motor action potential and sensory nerve action potential amplitudes. Summary statistics were used for demographic and clinical data. The t test and Wilcoxon signed rank test were used where appropriate. Results: Average follow-up was 18.6 months. Preoperatively, 20 patients had Medical Research Council less than or equal to grade 1 in hand intrinsics, small finger sensory nerve action potentials were absent in all patients except for three, and average compound motor action potentials were severely reduced (absent in nearly 40 percent) confirming severity. All groups had a statistically significant increase in strength. More than three-quarters of patients noted partial or complete resolution of clawing and intrinsic muscle wasting. Seventy-three percent of patients regained Medical Research Council greater than or equal to grade 3 and 47 percent achieved Medical Research Council greater than or equal to grade 4. Mean time to observation of nascent units was 8.5 months, and 77 percent of patients demonstrated an augmentation of motor unit numbers with forearm pronation on needle electromyography Conclusion: Proximal subcutaneous ulnar nerve transposition when combined with reverse end-to-side anterior interosseous nerve–to–ulnar nerve transfer demonstrates significant clinical and electrodiagnostic improvement of intrinsic muscle function. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.